2016
DOI: 10.1016/j.jaci.2015.06.037
|View full text |Cite
|
Sign up to set email alerts
|

Group 2 innate lymphoid cells mediate ozone-induced airway inflammation and hyperresponsiveness in mice

Abstract: Background Patients with asthma are highly susceptible to air pollution and in particular, to the effects of ozone (O3) inhalation, but the underlying mechanisms remain unclear. Objective Using mouse models of O3-induced airway inflammation and hyperresponsiveness (AHR), we sought to investigate the role of the recently discovered group 2 innate lymphoid cells (ILC2). Methods C57BL/6 and Balb/c mice were exposed to Aspergillus fumigatus and/or O3 (2ppm, 2h). ILC2 were isolated by FACS sorting and studied f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
108
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(116 citation statements)
references
References 36 publications
6
108
2
Order By: Relevance
“…demonstrated that the intratracheal instillation of particulate matter resulted in the death of alveolar macrophages and release of IL‐1α, which mediated the development of type 2 responses and allergic sensitization upon subsequent exposure to allergens. Furthermore, the induction of TSLP and IL‐33 by components of air pollution may also augment the function of ILCs that are important in allergic airway sensitization …”
Section: Potential Roles For Obesity and High‐fat Diet And Air Pollutmentioning
confidence: 99%
“…demonstrated that the intratracheal instillation of particulate matter resulted in the death of alveolar macrophages and release of IL‐1α, which mediated the development of type 2 responses and allergic sensitization upon subsequent exposure to allergens. Furthermore, the induction of TSLP and IL‐33 by components of air pollution may also augment the function of ILCs that are important in allergic airway sensitization …”
Section: Potential Roles For Obesity and High‐fat Diet And Air Pollutmentioning
confidence: 99%
“…ILC2s are abundant in the liver, lungs, skin, and gut [10]. Characteristic surface markers and receptors for chemokines, which are involved in the distribution of lymphoid cells to specific organ sites, are expressed by ILC2s [11]. Two transcription factors, RORα and GATA3, which are stimulated by IL-7, are required for the development of ILC2s [12].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to allergens, ambient air pollutants such as ozone can also cause asthma. ILC2s have been shown to mediate ozone‐induce AHR and airway inflammation . In this allergen‐independent asthma, both eosinophils and neutrophils are increased in the lungs and there is evidence that both ILC2s and γδ T cells are involved .…”
Section: Role Of Ilc2s In Disease Pathogenesismentioning
confidence: 91%
“…ILC2s have been shown to mediate ozone‐induce AHR and airway inflammation . In this allergen‐independent asthma, both eosinophils and neutrophils are increased in the lungs and there is evidence that both ILC2s and γδ T cells are involved . Interestingly, there has been a strain difference in ozone sensitivity with BALC/c being more sensitive than B6 .…”
Section: Role Of Ilc2s In Disease Pathogenesismentioning
confidence: 96%